The child adoption marketplace: Parental preferences and adoption outcomes - Mark Skidmore; Gary Anderson; Mark Eiswerth (Center for Economic Studies and ifo Institute (CESifo), 2011)
In the United States child adoption costs vary considerably, ranging from no out-of-pocket expense to 50,000 or more. What are the underlying causes for the variability in child adoption expenses? While cost variability is widely acknowledged, the sources of the differentials have not been systematically examined. This research considers the possibility that adoption cost differentials are determined by adoptive parent preferences for adoptive child characteristics. We administered a detailed survey to a sample of Michigan adoptive families to link adoptive parent characteristics, child characteristics, and adoption-related expenses and subsidies. We then use these data to estimate hedonic regressions in which adoption cost is a function of child characteristics. Our findings show that as much as 66 percent of the variation in cost is explained by child characteristics. Adoption costs are lower for older children, special needs children, and children of African descent. To our knowledge, this research is original in its application of hedonic analysis to child adoption decisions. Findings of the study inform policies regarding the transition of children from foster care to adoptive families and may help to determine appropriate subsidies aimed at achieving permanency and improved overall child well-being.
Keywords: D10; 330; child welfare; adoption; subsidy; Familienrecht; Eltern; Präferenztheorie; Kinder; Lebensqualität; Kosten-Nutzen-Analyse; Subvention; USA